EGF Induces Migration Independent of EMT or Invasion in A549 Lung Adenocarcinoma Cells - Schelch, Karin; Vogel, Lisa; Schneller, Anja; Brankovic, Jelena; Mohr, Thomas; Mayer, Rupert L.; Slany, Astrid; Gerner, Christopher; Grusch, Michael (Frontiers in Cell and Developmental Biology, 2021)
Tumors and the tumor microenvironment produce multiple growth factors that influence cancer cell behavior via various signal transduction pathways. Growth factors, like transforming growth factor beta (TGFβ) and epidermal growth factor (EGF) have been shown to induce proliferation, migration and invasion in different cell models. Both factors are frequently overexpressed in cancer and will often act in combination. Although both factors are being used as rational targets in clinical oncology, the similarities and differences of their contributions to cancer cell migration and invasion are not fully understood. Here we compared the impact of treating A549 lung adenocarcinoma cells with TGFβ, EGF and both in combination by applying videomicroscopy, functional assays, immunoblotting, real-time PCR and proteomics. Treatment with both factors stimulated A549 migration to a similar extent, but with different kinetics. The combination had an additive effect. EGF-induced migration depended on activation of the mitogen-activated protein kinase (MAPK) pathway. However this pathway was dispensable for TGFβ-induced migration, despite a strong activation of this pathway by TGFβ. Proteome analysis (data are available via ProteomeXchange with identifier PXD023024) revealed an overlap in expression patterns of migration-related proteins and associated gene ontology (GO) terms by TGFβ and EGF. Further, only TGFβ induced the expression of epithelial to mesenchymal transition (EMT)-related proteins like matrix metalloproteinase 2 (MMP2). EGF, in contrast, made no major contribution to EMT marker expression on either the protein or the transcript level. In line with these expression patterns, TGFβ treatment significantly increased the invasive capacity of A549 cells, while EGF treatment did not. Moreover, the addition of EGF failed to enhance TGFβ-induced invasion. Overall, these data suggest that TGFβ and EGF can partly compensate for each other for stimulation of cell migration but abrogation of TGFβ signaling may be more suitable to suppress cell invasion.